THE ROLE OF WOMEN FARMERS' HUMAN RESOURCES IN PRODUCTION ACTIVITIES IN CORN FARMING IN KARO DISTRICT, NORTH SUMATRA PROVINCE - Surbakti, Supriadi; Nasution, Zulkifli; Sihombing, Marlon; Thoha, Achmad Siddik (Journal of International Conference Proceedings, 2024)
The food crop commodity whose production continues to be increased to support national food needs is corn. Karo Regency is the largest corn producer in North Sumatra. In production activities on corn farming, the role ratio between the human resources of male farmers and female farmers is balanced, but the ratio of workers is more female farmers than male farmers. This research aims to analyze the role of female farmers' human resources in production activities and decision making in corn farming in Karo Regency. This type of research is a quantitative research method. The method for determining the research area was carried out purposively. The sampling method was carried out using Nonprobability Sampling using the Accidental Sampling technique. The data analysis method is in the form of qualitative and quantitative analysis based on the primary data and secondary data obtained. The research results show that the amount of labor provided by female farmers is higher than that of male farmers and the contribution of female farmers in decision making is very influential in production activities in corn farming in Karo Regency. Keywords: Human Resources, Women Farmers, Production, Corn Farming